The Implementation of Good Governance Concept In Letter Evidence Submission Regulation For E-Litigation Cases - Rina Elsa Rizkiana; Michael Gerry (Veteran Law Review, 2023)
The modernisation of public institutions aims to address issues of openness and community accountability of public institutions as well as making public services more responsive to the needs and aspirations of the community. The judiciary also complies with the community's requests that it implement the fundamentals of sound government. The 2010–2035 Judicial Reform Blueprint, which stresses using information technology to restructure and supports this. E-Litigation is a byproduct of Indonesia's judicial reforms. SK KMA RI Number 129/KMA/SK/VIII/2019 and PERMA 1 of 2019 provide as the legal foundation for electronic litigation. The principles outlined in the idea of good governance in terms of legal philosophy must be followed in the implementation of e-Litigation. This is in accordance with the principles of good governance, which deal with regulations pertaining to the validity of evidence submitted in e-Litigation of civil cases, that are responsive, effective, and efficient at the implementation stage. This research intends to examine the concepts of good governance, the legal foundation for e-Litigation in Indonesia, and the application of responsive, effective, and efficient principles to control the admissibility of documentary evidence in e-Litigation in civil cases. By taking a statutory method, this study adopts a normative approach to law. According to the study's findings, Indonesia's regulations on the admissibility of evidence in civil e-Litigation cases obstruct the fulfillment of responsive, effective, and efficient e-Litigation implementation principles. As a result, the legal framework of the rule governing the admissibility of evidence in Indonesian civil e-Litigation has to be modified to comply with good governance principles.